Analisis Perbandingan Kinerja Keuangan Bank Syariah dan Bank Konvensional di Indonesia - Tamimah (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2026)
The development of the banking system in Indonesia has shown significant dynamics through the implementation of a dual banking system consisting of Islamic banks and conventional banks. Differences in operational principles between the two banking systems influence financial performance, profitability, capital stability, and risk management within each banking institution. An analysis comparing financial performance is important to provide an overview of the effectiveness and competitiveness of Islamic and conventional banks in supporting national economic stability. This study employed a qualitative descriptive method using a literature review approach through secondary data obtained from financial reports, scientific journals, and related references during the 2019–2023 period. The indicators used include Return on Assets (ROA), Return on Equity (ROE), Capital Adequacy Ratio (CAR), Non-Performing Financing/Loan (NPF/NPL), and Financing to Deposit Ratio (FDR) and Loan to Deposit Ratio (LDR). The results indicate that conventional banks have higher profitability levels than Islamic banks, particularly in ROA and ROE ratios, due to larger business scales, diversified income sources, and more efficient operational management. On the other hand, Islamic banks demonstrate better capital stability and risk management through relatively higher CAR ratios and more stable control of non-performing financing. In addition, Islamic banks show promising growth potential, especially in MSME financing and profit-sharing-based financing sectors. Strengthening financial literacy, service digitalization, and optimizing risk management are essential strategies to improve competitiveness and ensure the sustainability of the banking sector in Indonesia.